Java: The Complete Reference, Twelfth Edition - Schildt, Herbert (McGraw-Hill's AccessEngineeringLibrary, 2022)
Fully updated for Java SE 17, Java: The Complete Reference, Twelfth Edition explains how to develop, compile, debug, and run Java programs. Best-selling programming author Herb Schildt covers the entire Java language, including its syntax, keywords, and fundamental programming principles. You'll also find information on key portions of the Java API library, such as I/O, the Collections Framework, the stream library, and the concurrency utilities. Swing, JavaBeans, and servlets are examined, and numerous examples demonstrate Java in action. Of course, recent additions to the Java language, such as records, sealed classes, and switch expressions are discussed in detail.